Efficacy of Electroconvulsive Therapy in Bipolar Disorder with Mixed Features. (5th January 2016) - Palma, Miguel; Ferreira, Berta; Borja-Santos, Nuno; Trancas, Bruno; Monteiro, Céu; Cardoso, Graça
Abstract : Introduction. Mixed states represent a frequent presentation of bipolar disorder, associated with higher resistance to psychopharmacology. Limited evidence supports the use of ECT in these patients. We aim to report our experience on treating bipolar mixed states with ECT. Methods. Retrospective data were collected from all bipolar patients submitted to acute ECT treatment, between June 2006 and June 2011. Three groups were created in terms of affective polarity of the episode. CGI rating was used to establish clinical remission and demographic and clinical variables were compared among groups. Long-term outcome was assessed through readmission measures, considering the use of continuation or maintenance ECT. Results. During the study time frame, a total of 50 ECT course treatments were performed on 41 bipolar patients. All affective episodes, except one mixed state, showed a positive clinical response. Patients with mixed state presentation tended to be younger and have an earlier first hospitalization than depressed patients. No differences were found in terms of ECT sessions performed, length of hospital admission, referral to continuation ECT treatment, number of readmissions, and time until next readmission. Conclusions. Our results support the effectiveness of ECT in patients experiencing a mixed affective state.